Effect of different dietary oil sources on the performance, egg quality and antioxidant capacity during the late laying period - Mengmeng Xu; Le Liu; Zongze Fan; Lizhu Niu; Wenxi Ning; He Cheng; Mengyun Li; Wenying Huo; Pan Zhou; Hongyu Deng; Wen Chen; Long Che (Poultry Science)
This study investigated the effects of different dietary ratios of linseed and soybean oils on the performance, egg quality, and antioxidant capacity of late-phase laying hens. A total of 360 70-week-old Jinghong laying hens were randomly assigned to four groups of six replicates each, with 15 chickens per replicate. Diets with linseed oil to soybean oil ratios of 3:0 (T1), 2:1 (T2), 1:2 (T3), and 0:3 (T4) were fed for 4 weeks. No significant differences in egg weight, feed intake of laying hens, egg production, or feed-to-egg ratio (P > 0.05) were observed among the groups. Compared with the T4 group, the T2 group had a significantly higher number of 8–10 mm follicles. Moreover, albumen height and Haugh units were significantly higher in the T3 group than in the T4 group (P < 0.05), although significant differences were not observed among the T1, T2, and T3 groups. With an increase in linseed oil addition to the feed, the content of n-3 polyunsaturated fatty acids in chicken eggs significantly increased (P < 0.05). Compared to the T4 group, the addition of linseed oil to the diet significantly reduced the blood malondialdehyde content and increased the blood glutathione peroxidase (GSH-PX) and superoxide dismutase enzyme activity. The GSH-PX activity and total antioxidant capacity in the oviducts of the T3 group were significantly higher than those of the T4 group (P < 0.05). The protein expression levels of Nrf2, HO-1, and NQO-1 in the oviduct tissues were significantly higher in the T3 group than in the T4 group (P < 0.05). This study showed that a linseed oil to soybean oil ratio of 1:2 in the T3 group enhanced egg quality by reducing oxidative stress and improving the oviduct microenvironment.